If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(5x + 5) = -40 + -1x Reorder the terms: -8(5 + 5x) = -40 + -1x (5 * -8 + 5x * -8) = -40 + -1x (-40 + -40x) = -40 + -1x Add '40' to each side of the equation. -40 + 40 + -40x = -40 + 40 + -1x Combine like terms: -40 + 40 = 0 0 + -40x = -40 + 40 + -1x -40x = -40 + 40 + -1x Combine like terms: -40 + 40 = 0 -40x = 0 + -1x -40x = -1x Solving -40x = -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. -40x + x = -1x + x Combine like terms: -40x + x = -39x -39x = -1x + x Combine like terms: -1x + x = 0 -39x = 0 Divide each side by '-39'. x = 0 Simplifying x = 0
| 1a^2-8a-20=0 | | (-1)(d+5)=11.4 | | 100/736 | | 6(1+4x)=-3x-21 | | -5x+2=-28 | | 1x^2-2x-15=0 | | 7y/12-2=5y/8 | | 17.50(x+4)=315.00 | | 7x^2-100=-2x^2+125 | | (4x^2-5x^3)-(8x^2-7x^3)= | | X^2+y^2-10x-6y+18=0 | | 3g-1/9-g-1/6 | | (3w-10)w=77 | | 4.2q-1.8q=-1.6q-1.7 | | 7x^2-100=2x^2+125 | | (-5/(4y+16))+1=(8/(y+4)) | | 50lbs-24oz= | | -7=4w-9 | | y-(-1)=(6/7)(x-8) | | X^2+y^2-10x-2a+17=0 | | 4.5n-5=2+1.8 | | S=C-rC | | y=-6/7x+1 | | 13x^2+56x+75=4x^2-10x-46 | | (x^(1/5)+25x)/x | | -2/-7 | | (1/4)x-1=0 | | 3/4p-12=27 | | [p-15]=26 | | -2=-7y | | 3f*15=48 | | -5(1-6r)=7(11r+6) |